How Histone Deacetylase Inhibitors Alter the Secondary Metabolites of Botryosphaeria mamane, an Endophytic Fungus Isolated from Bixa orellana. Issue 4 (20th March 2019) - Triastuti, Asih; Vansteelandt, Marieke; Barakat, Fatima; Trinel, Manon; Jargeat, Patricia; Fabre, Nicolas; Amasifuen Guerra, Carlos A.; Mejia, Kember; Valentin, Alexis; Haddad, Mohamed
Abstract: Fungi are talented organisms able to produce several natural products with a wide range of structural and pharmacological activities. The conventional fungal cultivation used in laboratories is too poor to mimic the natural habitats of fungi, and this can partially explain why most of the genes responsible for the production of metabolites are transcriptionally silenced. The use of Histone Deacetylase inhibitors (HDACis) to perturb fungal secondary biosynthetic machinery has proven to be an effective approach for discovering new fungal natural products. The present study relates the effects of suberoylanilide hydroxamic acid (SAHA) and sodium valproate (VS) on the metabolome of Botryosphaeria mamane, an endophytic fungus isolated from Bixa orellana L. UHPLC/HR‐MS analysis, integrated with four metabolomics tools: MS‐DIAL, MS‐FINDER, MetaboAnalyst and GNPS molecular networking, was established. This study highlighted that SAHA and VS changed metabolites in B. mamane, causing upregulation and downregulation of metabolites production. In addition, twelve compounds were detected in the extracts as metabolites structurally correlated to SAHA, indicating its important reactivity in the medium or its metabolism by the fungus. An addition of SAHA induced the production of eight metabolites while VS induced only two metabolites undetected in the control strain. This result illustrates the importance of adding HDACis to a fungal culture in order to induce metabolite production. Abstract :